Vascular changes after vitrectomy for rhegmatogenous retinal detachment: optical coherence tomography angiography study. Issue 5 (26th November 2019) - Bonfiglio, Vincenza; Ortisi, Elina; Scollo, Davide; Reibaldi, Michele; Russo, Andrea; Pizzo, Alessandra; Faro, Giuseppe; Macchi, Iacopo; Fallico, Matteo; Toro, Mario D.; Rejdak, Robert; Nowomiejska, Katarzyna; et al.
Abstract: Purpose: To analyse the postoperative foveal avascular zone (FAZ) area, superficial vessel density (SVD) and deep vessel density (DVD) and their correlation with functional (best‐corrected visual acuity, BCVA) and anatomical outcomes (foveal macular thickness, FMT) after surgery for rhegmatogenous retinal detachment (RRD) repair. Method: Patients with RRD eyes, successfully treated with a single pars plana vitrectomy (PPV) with gas tamponade and a minimum 12 months follow‐up, were re‐examined. Foveal avascular zone (FAZ) area, SVD, DVD and FMT were evaluated by using optical coherence tomography angiography (OCTA) and compared to fellow eye. Results: Fifty‐six patients with macula‐on and 37 with macula‐off RRD were included in the study. In both groups, no difference in FMT and FAZ area was found compared to fellow eyes. In macula‐on RRD eyes, a lower parafoveal DVD (p = 0.001) was detected; FAZ area was related to FMT (p = 0.025), and the postoperative BCVA was correlated with parafoveal DVD (p = 0.010) and FAZ area (p = 0.003). In macula‐off RRD eyes, lower parafoveal SDV (p = 0.012), and foveal and parafoveal DVD (p = 0.012 and p < 0.001, respectively) were observed. BCVA was related to FAZ area (p = 0.012), foveal SVD (p = 0.005) and parafoveal DVD (p = 0.010). Conclusion: Rhegmatogenous retinal detachment eyes successfully treated with PPV had lower vessel density in the superficial and deep retinal plexus compared to fellow healthy eyes; BCVA was related to FAZ area and vessel density.